Evaluation of Antimicrobial or Non-antimicrobial Treatments in Commercial Feedlot Cattle With Mild Bovine Respiratory Disease Based on a Refined Case-Definition - Nickell, Jason; Bryant, Lonty; Lechtenberg, Kelly F.; Cull, Charley (Frontiers in Veterinary Science, 2020)
The study objective was to compare clinical and performance outcomes among feedlot steers treated for bovine respiratory disease (BRD) with tildipirosin (TIL), flunixin transdermal solution (FTS; topical application), or both, based on a refined BRD case-definition. Crossbred steer calves (N=2,380) were enrolled based on a clinical illness score (CIS) of 1 to 3; a rectal temperature between > 102.5° F and < 103.9° F; and a Whisper Score (WS) = 1 or > 2. Within each WS stratum, steers were randomly allocated to Saline, TIL, FTS, or TIL + FTS to reflect a 2x2 factorial design. Individual health and performance outcomes were measured on Day 60 and closeout. From Day 0 through Day 60, in both strata, TIL resulted in significantly (P < 0.05) fewer BRD retreatment events, fewer 3rd BRD treatments, fewer steers that did not finish, and greater average daily gain when compared to steers that were not treated with TIL. From Day 0 through closeout, cattle with a WS > 2, treated with TIL had fewer animals (P < 0.05) that did not finish compared to steers not treated with TIL. In this study, feedlot steers with clinical signs of BRD and rectal temperatures lower than traditional cutoffs displayed a positive response to antimicrobial therapy. A clear benefit of FTS was not observed in this study. Calves with a WS ≥ 2 were lighter at the time of first BRD treatment compared to calves with a WS=1. However, standalone TIL therapy was the optimal BRD treatment modality across WS strata in this study.